UMP suspends academic operations a week starting 22 December 2021 - Mimi Rabita, Abdul Wahit (2021)
PEKAN, 22 December 2021 - Considering the current situation and after evaluating every aspect, the university management has agreed to suspend all academic activities at Universiti Malaysia Pahang (UMP) effective from 22 to 28 December 2021.